Protection Of Trade Unions Based On Positive Law In Indonesia - Sihombing, Daulat (Inspiring Law Journal, 2024)
Workers must know and understand that as individuals and workers, not much can be achieved. So that on its journey, several workers or what are commonly known as laborers form labor unions to protect their rights and reduce forms of exploitation carried out by company management. In the course of history, it has been proven that the role of labor unions in fighting for the rights of their members is very large, so that workers have felt the benefits of independent labor union organizations that are consistent in fighting for labor rights. Considering that the labor factor in this development process must be considered, therefore efforts are needed to foster, direct and protect the workforce to create welfare related to what they do. The nature contained in Article 3 of Law No. 21/2000 is emphasized that labor unions, federations and confederations of labor unions are free, open, independent, democratic, and responsible. Open means that in accepting members and or fighting for the interests of workers, labor unions, federations and confederations of labor unions do not differentiate between political affiliations, religion, ethnicity, and gender. The purpose of labor unions, federations and confederations of labor unions is to provide protection, defend the rights and interests and improve decent welfare for workers and their families. Examples of clauses that support the interests of workers are clauses that emphasize the terms of work, social security for workers, labor rights, and others